Role of livestock in ensuring food security in India - Prasad, C. S.; Anandan, S.; Gowda, N. K. S.; Giridhar, K. (Indian Farming, 2015)
India has one of the largest livestock population in the world. This sector makes a significant contribution towards the national economy, besides enhancing household food security. Livestock contributes towards milk, meat, eggs, manure and draught needs of the population of our country. The need today is to realize the gaps between the demand and supply, diminishing this gap, better R&D facilities and efficient management of the livestock to improve the productivity. Only then, in the future, the livestock sector can fulfill the gap of nutrition that is presently lacking.